Salivary Acetylcholinesterase Activity Is Increased in Parkinson’s Disease: A Potential Marker of Parasympathetic Dysfunction - Tatyana Fedorova; Cindy Soendersoe Knudsen; Kim Mouridsen; Ebba Nexo; Per Borghammer (Parkinson's Disease)
Introduction. Decreased salivary flow and xerostomia are frequent findings in Parkinson’s disease (PD), possibly caused by alterations in the parasympathetic tonus. Here we explore salivary acetylcholinesterase (AChE) activity as a potential biomarker in PD. Methods. We measured salivary flow, AChE activity, and total protein concentration in 30 PD patients and 49 healthy controls. We also performed exploratory correlation analyses with disease duration, motor symptom severity, autonomic complaints, and other nonmotor symptoms. Results. PD patients displayed significantly decreased salivary flow rate, significantly increased salivary AChE activity, and total protein concentration. Importantly, the AChE activity/total protein ratio was significantly increased in PD patients, suggesting that increased AChE activity cannot be explained solely by upconcentration of saliva. The Unified PD Rating Scale (UPDRS) score displayed significant correlation with total salivary protein (P=0.002) and near-significant correlation with salivary flow (P=0.07). Color vision test scores were also significantly correlated with AChE activity (P=0.04) and total protein levels (P=0.002). Conclusion. Salivary AChE activity is increased in PD patients compared to healthy controls. Future studies are needed to elucidate whether this parameter reflects the extent of neuronal damage and parasympathetic denervation in the salivary glands of PD patients.